Management of genetic syndromes - 4 0 16; Cassidy, Suzanne B.;Allanson, Judith E.; 5 (New York : Wiley-Liss, 2001)
A guide to genetic syndromes and disorders that provides information on each syndrome's etiology, natural history, diagnosis, symptoms, evaluation, treatment and management, and more.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; diagnosis;therapy;diagnosis;therapy -- Genetic disorders.;Hereditary Diseases;Hereditary Diseases;Abnormalities, Multiple;Abnormalities, Multiple;Birth defects.;Genetics.; 20; 2